The diatoms of Acadia National Park, Maine, with a detailed account of the Eunotiophycidae - Veselá, Jana (Jihočeská univerzita, 2010)
Taxonomy of diatoms (Bacillariophyceae) was studied in 45 samples from Acadia National Park, Maine, U.S.A. Approximately 550 diatom taxa in 87 genera were observed in the samples from various habitats (i.e., lakes, streams, wetlands, wetwalls and brackish habitats). The most species rich group of diatoms, Eunotiophycidae, was studied in detail, resulting in a detailed documentation of 81 species and varieties with 18 probably new taxa.
The diatoms of Acadia National Park, Maine, with a detailed account of the Eunotiophycidae
Keywords: Eunotiophycidae; Acadia National Park; Maine; diatoms; Eunotiophycidae; Acadia National Park; Maine; diatoms